The Significance of Educational Psychology in Islamic Religious Education Learning - Husneti, Lira; Fitriani, Wahidah (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2023)
During the process of Islamic religious education, there is a dynamic exchange of information and ideas between the teachers and pupils. In this contact, the teacher must comprehend the conduct of each pupil, who originates from diverse family backgrounds, cultures, and their own capabilities. Hence, there is a want for scientific disciplines that can comprehend the conduct and attributes of students. The subject under consideration is educational psychology. The research seeks to ascertain the significance or function of educational psychology in the acquisition of knowledge in Islamic religious education. This study employs a library-based research methodology, in which the data is gathered from a variety of literary sources, including books, papers, and pertinent records, that pertain to the stated subject. The research findings demonstrate the crucial importance of educational psychology in Islamic religious education. Proficiency in educational psychology enables educators to comprehend the individual circumstances of each student, hence equipping teachers with valuable insights.